Peran Mahasiswa KKN STIM Lasharan Jaya dalam Mewujudkan Desa Wisata Agro melalui Pembangunan Ikon Desa Bontomarannu - Galib, Mukhtar; Muharram, Muharram; Kusumaningrum, Retno Ayu; Pamungkas, Alfian; Fatwa, M; Watiana, Watiana; Riska, Riska; Appang Allo, Meli Banne (ABDI DAYA: Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2025)
Bontomarannu Village, located in Uluere District, Bantaeng Regency, has significant potential to be developed into an agro-tourism destination due to its cool climate and fertile volcanic soil, which support horticultural farming. The village has long been a hub for producing high-quality vegetables, such as chili, tomatoes, and potatoes. This study examines the role of STIM Lasharan Jaya KKN students in developing a village icon as a promotional strategy for community-based tourism and local empowerment. Through a participatory approach, the students and the village community collaboratively designed and constructed an icon reflecting the village's unique identity. The icon, consisting of large letters spelling "Bontomarannu," serves as a visual landmark and symbol of local identity. The results demonstrate that the icon not only functions as a striking visual attraction but also attracts visitors, creates new economic opportunities, and strengthens the community’s sense of ownership and pride. In addition to promoting agro-tourism potential, the project enhanced cross-sector collaboration between the community, students, and local government. This study underscores the importance of participatory and sustainable approaches in developing agro-tourism villages, which can provide long-term economic, social, and cultural benefits for the local community